Analisis autokorelasi spasial tingkat pengangguran di Provinsi Jawa Barat pada tahun 2019 - Mahara, Duhania Oktasya; Anbarwati, Fitriyah Nisrina; Cintami, Alya; Safira, Muthia Citra; Hariani, Nabila Puspa; Ulfa, Siti Mariah; Tiyara, Usi; Widodo, Edy (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Unemployment is a term toward people who there is no vocation, a quest for work, or are trying to get a decent job. Unemployment is a problem that can approach the economy that causes poverty and other matter as social problems. In Indonesia, West Java became the province with the second-highest unemployment rate after Banten at 7.99%. Then, this might occur due to the neighborliness factor or closeness between regions, so it is necessary to re-examine the pattern of unemployment rate spread that occurred in the province of West Java. The purpose of this research to determine the pattern of the spread of unemployment rates from each district in the province of West Java. The method used is the spatial autocorrelation of Moran’s I. This method is very important in finding information about the pattern of distribution/grouping characteristics of an observation location and its relation to other observation locations. The results of this spatial autocorrelation analysis obtained the conclusion that there is a positive spatial autocorrelation which shows the similarity of values ​​between regions and indicates the value of the unemployment rate between regions in West Java Province